DETERMINING THE INFLUENCE OF FINISHING PROCESSING OF KNITTED FABRICS ON THEIR SEWING PROPERTIES - HIBELINDA, OLENA; SARIBYEKOVA, YULIYA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
Knitwear occupies a special place among the materials used for clothing production. It not only has an attractive appearance, but is also a fairly practical material. Products made from knitted fabrics are used in almost all areas of human life, it can be both household and special clothing.Consumers have appreciated the high consumer characteristics of the material, purchasing various items made from knitted fabrics. Knitwear occupies a special place among the materials used for clothing production. Consumers have appreciated the high consumer characteristics of the material, purchasing various items made from knitted fabrics. One of the key challenges in the application of knitted fabrics for garment manufacturing, in contrast to woven fabrics, lies in their potential to undergo significant dimensional changes when subjected to mechanical interaction with the working elements of technological equipment. This characteristic introduces additional complexities at the stages of fabric preparation, cutting, and assembly, while also impeding the achievement of stable structural parameters in the final product. The technological processing of garments made from knitted fabrics is characterized by specific requirements and considerations, primarily determined by the inherent properties of the material. Knitted fabrics stretch during sewing, so to achieve high-quality stitching, you need to change the pressure of the foot on the material to improve advancement, loosen the thread tension, and use special needles. The study shows the possibility of improving the technological characteristics of knitted fabric by applying innovative finishing with the use of organosilicon softeners. The influence of organosilicon softeners on the indicators of technological properties of knitted fabric was determined: deformation properties, stability of linear dimensions, productivity of a sewing machine. It was established that the finishing of knitted fabric using the drug Kolosoft P allows to improve its sewing properties and can potentially ensure an increase in the quality of finished products.
Keywords: knitted fabrics; technological properties; of finishing processing; sewing products; productivity of a sewing machine